Individual and Synergistic Effects of Pesticides Chlorpyrifos and Dimethoate on Oxygen Consumption in Macrobrachium Rosenbergii (De Man) - V . N. Hegde; V. V. Dalvie (Journal of Indian Fisheries Association, 2023)
The advent of “Green Revolution” has brought with it the inadvertent use of pesticides. In past, studies were carried out on the eﬀects of individual pesticides on living organisms. Later studies showed that while many pesticides may accumulate in the organisms causing long term changes in them some pesticides, which enter the ecosystem can also enhance the eﬀects of other pesticides. In the present study, an attempt has been made to see the individual and synergistic eﬀects of two organophosphorous pesticides, Chlorpyrifos and Dimethoate, on the giant freshwater prawn Macrobrachium rosenbergii (De Man), in terms of oxygen consumption observed over a period of 24 hrs, 48 hrs and 72 hrs. The rate of oxygen consumption can be taken as a parameter to observe the sub lethal eﬀects of the pesticides. The animals showed stress in irst 24 hours of exposure with respect to oxygen consumption under the treatment of pesticides. In case of eﬀects of individual pesticide, Chlorpyrifos caused greater stress than Dimethoate as compared with the control group. Similarly, it was also observed that synergistically Dimethoate enhances (positive synergism) eﬀect of Chlorpyrifos leading to greater toxic eﬀects even at lower concentrations, in the first 24 hours.